Periodontal Destruction in a Child with Habit Disorder A Case Report - m Khosravi Samani, (Babol University of Medical Sciences, 2010)
BACKGROUND AND OBJECTIVE: Self-inflicted injuries are created following involuntary hurt of patients to themselves. Patients often are not aware of these injurious habits. These injuries in oral region can result to gingival hyperkeratosis, swelling, ulceration and recession or gingivitis and periodontitis. This article is a case report of periodontal destruction in a child with a habit disorder.CASE: A 11-year-old boy with the chief complaint of severe gingival swelling and pain of lingual aspect of anterior lower teeth with mobility was referred. At first visit a large periodontal abscess (probing depth 11mm) was observed. In patients history, it was detected that he had a habit of fingernail wedging between the teeth which had been following a severe stress from 4 years ago. After making aware of the injurious habit and recommendation of its evacuation and referral to the psychiatrist the patient received first phase of periodontal treatment along with odontoplasty and antibiotic therapy. After 3 months complete periodontal health had been provided.CONCLUSION: In this case, diagnosis and omitting of the destructive oral habit resulted in improvement of all periodontal signs of the teeth. One of the important points in diagnosis and treatment of these defects is attention to possible injurious oral habit due to emotional stress.